ANALYTICAL HIERARCHY PROCESS METHOD IN SELECTING ONLINE TRANSPORTATION IN MANADO (CASE STUDY: GOJEK, GRAB, AND UBER) - Burhanuddin, Rizka A.; Worang, Frederik G.; Tulung, Joy Elly (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract:. The online transportation is cheaper than a regular taxi fare in the city. Not only has the citizen, the online transportation also made the tourist easier to travel. The application also provides a several languages. The application also provides maps, which makes the consumer easier to find the place that they want to go to. This research aims to know which criteria is the most important for customer in selecting an online transportation in Manado and the most preferred online transportation for the customer. This research used analytical hierarchy process with the sample of 50 respondents that were obtained from citizen in Manado. The result from this research shown that price is the most important criteria for the consumer to choose an online transportation. The consumer wants an affordable price of the online transportation. Grab is the most preferred online transportation. Gojek and Uber as the competitors of Grab, should have to improve their performance, adding more promotions and make some different thing which is unique or something that the competitors does not haveÂ Keywords: consumer purchase decision, analytical hierarchy processÂ